2015
DOI: 10.1117/12.2184814
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking characterization of polymers based on their optical dispersion utilizing a white-light interferometer

Abstract: This work analyses samples of the widely used encapsulant of photovoltaics modules, ethylene vinyl acetate (EVA). The samples were cross-linked using a lamination technique for different curing times (0 - 20 minutes). The cross-linking characterization is done by determinating the material dispersion with the aid of a combined temporal- and spectral domain white-light interferometer. With the proposed technique it was possible to discriminate the differences in crosslinking for the given curing times. One impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…During the last years, several investigations on the crosslinking behavior of EVA have been published . Most of these publications deal with the question how to characterize the degree of crosslinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last years, several investigations on the crosslinking behavior of EVA have been published . Most of these publications deal with the question how to characterize the degree of crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these publications deal with the question how to characterize the degree of crosslinking. Next to Soxhlet extraction, mostly thermal and thermomechanical characterization methods were used, but recently also optical or spectroscopic methods based on Raman, luminescence spectroscopy or white‐light interferometry have been applied and proven successful . These methods can not only be applied to isolated EVA films but also to EVA laminated within PV modules allowing for an in‐line quality control of the degree of crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the derived optical thickness, a novel approach called WPDE was developed and successfully applied to the measurement of a negative tone resist sample. While previous works demonstrated that the fundamental method is capable of resolving differences in cross-linking degrees with high repeatability [ 31 ], the novel approach extended the method even further. It was demonstrated that the refractive index, derived from the optical thickness, can be measured with an accuracy of about 7.9 × 10 −5 as RMS error with regard to literature values.…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate the degree of cross-linking, the analysis of the refractive index can be utilized [31]. By rewriting Equation (1), the phase-term containing the refractive index can be extracted, cos1[]Imeas(x,λ)I0(λ)1=φ=2π[]nsmp(x,λ)1tsmp+[]nDE(λ)1tDEδλ.…”
Section: Methodsmentioning
confidence: 99%
“…where I0(λ) is the spectral profile of the light source and δ is the path length difference between both arms. In order to estimate the degree of cross-linking, the analysis of the refractive index can be utilized [8]. Therefore, the phase of the recorded signal was extracted from the interference data.…”
Section: Methodsmentioning
confidence: 99%